ANALISA PENGARUH KEBIJAKAN PEMBIAYAAN TERHADAP KEMAKMURAN PEMEGANG SAHAM - Sumanti, Elvis (JBE (Journal of Business and Economics); Volume 12 No.1, 2013 JBE UNKLAB, 2013)
This research aims to evaluate the significance of Indonesian manufacturing companies’ financial policies toward stockholders wealth maximization. The object of this study is Indonesian manufacturing companies listed in Indonesisa Stock Exchange during 2008-2012 This research uses simple regression analysis statistic method. Companies’ financial policies are proxied by DAR (debt to asset ratio) and DER (debt to equity ratio); stockholders wealth maximization proxied by stock price and dividend. This research finds that both DAR and DER positively significantly affect the stockholders wealth. Likewise, DAR has positive significant toward the stock return.